Degradation of macroalgal detritus in shallow coastal Antarctic sediments. (5th February 2019) - Braeckman, U.; Pasotti, F.; Vázquez, S.; Zacher, K.; Hoffmann, R.; Elvert, M.; Marchant, H.; Buckner, C.; Quartino, M. L.; Mác Cormack, W.; Soetaert, K.; Wenzhöfer, F.; et al.
Abstract: Glaciers along the western Antarctic Peninsula are retreating at unprecedented rates, opening up sublittoral rocky substrate for colonization by marine organisms such as macroalgae. When macroalgae are physically detached due to storms or erosion, their fragments can accumulate in seabed hollows, where they can be grazed upon by herbivores or be degraded microbially or be sequestered. To understand the fate of the increasing amount of macroalgal detritus in Antarctic shallow subtidal sediments, a mesocosm experiment was conducted to track 13 C‐ and 15 N‐labeled macroalgal detritus into the benthic bacterial, meiofaunal, and macrofaunal biomass and respiration of sediments from Potter Cove (King George Island). We compared the degradation pathways of two macroalgae species: one considered palatable for herbivores (the red algae Palmaria decipiens ) and other considered nonpalatable for herbivores (the brown algae Desmarestia anceps ). The carbon from Palmaria was recycled at a higher rate than that of Desmarestia, with herbivores such as amphipods playing a stronger role in the early degradation process of the Palmaria fragments and the microbial community taking over at a later stage. In contrast, Desmarestia was more buried in the subsurface sediments, stimulating subsurface bacterial degradation. Macrofauna probably relied indirectly on Desmarestia carbon, recycled by bacteria and microphytobenthos. The efficient cycling of the nutrients and carbon from the macroalgae supports a positive feedback loop among bacteria, microphytobenthos, and meiofaunal and macrofaunal grazers, resulting in longer term retention of macroalgal nutrients in the sediment, hence creating a food bank for the benthos.